2004
DOI: 10.1038/nature02447
|View full text |Cite
|
Sign up to set email alerts
|

Neural activity predicts individual differences in visual working memory capacity

Abstract: Contrary to our rich phenomenological visual experience, our visual short-term memory system can maintain representations of only three to four objects at any given moment. For over a century, the capacity of visual memory has been shown to vary substantially across individuals, ranging from 1.5 to about 5 objects. Although numerous studies have recently begun to characterize the neural substrates of visual memory processes, a neurophysiological index of storage capacity limitations has not yet been establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

186
1,755
15
16

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,617 publications
(2,047 citation statements)
references
References 29 publications
186
1,755
15
16
Order By: Relevance
“…In the no-shift task, a CDA component was expected to emerge during the delay period at posterior electrodes contralateral to the side of the task-relevant memorized objects, similar to previous findings (e.g., Vogel & Machizawa, 2004). The critical question was whether the size and polarity of this CDA component would be different in the horizontal shift task.…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…In the no-shift task, a CDA component was expected to emerge during the delay period at posterior electrodes contralateral to the side of the task-relevant memorized objects, similar to previous findings (e.g., Vogel & Machizawa, 2004). The critical question was whether the size and polarity of this CDA component would be different in the horizontal shift task.…”
Section: Introductionsupporting
confidence: 82%
“…Evidence for this comes from ERP studies of visual working memory (e.g., Vogel & Machizawa, 2004;McCollough, Machizawa, & Vogel, 2007). These studies employed a change detection paradigm where a bilateral memory display containing coloured objects in the left and right visual hemifield is preceded by a precue that instructs participants which side of this memory display they have to remember.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This limit has been attributed to activity in parietal areas [41][42][43] . However, further studies have shown that high-capacity individuals are more effi cient at fi ltering out irrelevant items, while low-capacity individuals cannot efficiently filter out such distractions [44] .…”
Section: Prefrontal Cortex and Wm Quantitymentioning
confidence: 99%